2021
DOI: 10.46827/ejes.v8i4.3698
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Gender Role Attitudes and Epistemological Beliefs of University Students

Abstract: In this study, the relationships between university students and their perceptions of gender roles and epistemological beliefs were investigated. Gender roles are a phenomenon that are determined by culture, and begin to emerge at an early age, which may include some stereotypical behaviors along with a number of attitudes, duties and obligations that the individual is expected to perform as a woman or a man. Epistemological belief is seen as an individual feature of how knowing and learning take place. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…31 It is stated that the cultural and social environment influences epistemological belief, and the social environment and sociocultural environments cause differences in individuals' knowledge, knowledge, learning processes, and, consequently, their epistemological beliefs. 19 In this study, the developed/mature BOOUT of which the students live in villages compared to those who live in provinces, districts, or towns means that they think knowledge can change due to its nature. When it is considered that understanding positive sciences and the basic way for the development in this area is the observance of nature, we can imply that village life offers this opportunity to students.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…31 It is stated that the cultural and social environment influences epistemological belief, and the social environment and sociocultural environments cause differences in individuals' knowledge, knowledge, learning processes, and, consequently, their epistemological beliefs. 19 In this study, the developed/mature BOOUT of which the students live in villages compared to those who live in provinces, districts, or towns means that they think knowledge can change due to its nature. When it is considered that understanding positive sciences and the basic way for the development in this area is the observance of nature, we can imply that village life offers this opportunity to students.…”
Section: Discussionmentioning
confidence: 97%
“…18 In a mixed method study conducted by Çuhadaroğlu with 517 students from two different universities, it was determined that gender was an important factor affecting the epistemological beliefs of university students. 19 Men living in a village had more BLDE than those living in provinces, districts, and towns. In the meta-analysis study by Kanadlı and Akay, in which they examined 37 studies on epistemological beliefs conducted with university students in Türkiye between 2005 and 2017, they have revealed that women's beliefs that learning depends on the effort are more developed than men.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all these studies, it was thought that it would be useful to investigate the effect of gender in the model examining the relationship between epistemological beliefs and learning approaches. Culturally adopted gender roles (Çuhadaroğlu, 2011) may differentiate students’ approaches to knowledge and learning in some dimensions. It is important to contribute to the literature in comparing the role of gender in the relationship between epistemological beliefs and learning approaches in the context of different cultures.…”
Section: Introductionmentioning
confidence: 99%